Meiotic abnormalities in cultivated and synthetic hexaploid wheat and their hybrids - Kandalkar, Vasant shridharrao; Pachauri, Preeti (Journal of Cereal Research, 2015)
Hexaploid wheat has no close relative species at the hexaploid ploidy level. Synthetic hexaploid wheat, produced by crossing Triticum turgidum L. spp (2n=4x=28, AB genomes) with A. tauschii Coss. (2n=2x=14, D genome), is considered a promising source of exotic alleles for introgression into wheat. Six varieties and 4 interspecific crosses included different species i.e. Triticum aestivum, Triticum durum, Triticum dicoccum and synthetic hexaploid wheat grown in single row plot during Rabi 2013-14. Â Immature spikes were collected at morning time between 5 to 7 oâ€™clock and ï¬xed in Carnoyâ€™s solution and stained with acetocarmine.Pollen mother cells (PMCs) from anthers of diï¬€erent stages of meiotic process were analysed for their chromosomal behaviour and irregularities. Meiotic abnormalities such as laggards, chromosome bridges, micronuclei, chromosome stickiness, ring bivalent and precocious chromosome migration were observed in different meiotic stages. The results revealed that maximum ring bivalents, micronuclei, laggard chromosomes, chromosome stickiness and precocious chromosome migration were observed in interspecific crosses viz., â€˜SYNTHETIC-21 X DDK-1038â€™, â€˜SYNTHETIC-19 X HI-8498â€™, â€˜SYNTHETIC-18 X RD-1336â€™, DDK-1038 and â€˜SYNTHETIC-18 X RD-1336â€™ compared to their parents. These various meiotic abnormalities in inter-specific crosses revealed that synthetic lines may arises new meiotic abnormalities but these can be used as new source for transferring the desired traits to cultivated wheat.